Multicolour and nearly white light emission in YP0.8V0.2O4:Sm3+ nanorods: controlled energy transfer - Singh, N.S. (Journal of Alloys and Compounds, 2017)
Nanorods of YP0.8V0.2O4:Sm³⁺ have been synthesized under hydrothermal conditions. Substitution of vanadium (V⁵⁺) sites in YVO4 by phosphorus ions (P⁵⁺) has been confirmed by Fourier transform infrared spectroscopy, X-ray diffraction and transmission electron microscopy. Careful selection of Sm³⁺ concentration in YP0.8V0.2O4 enables to achieve the controlled energy transfer from the VO4³⁻ absorption to the excited states of Sm³⁺ ions. The controlled energy transfer has been confirmed from the steady state luminescence and decay lifetime studies of VO4³⁻ emission. With the controlled retention of VO4³⁻ emission, tuning of light emission from the singly (Sm³⁺) doped YP0.8V0.2O4 nanorods is realized. At a particular doping concentration of Sm³⁺ (1.25 at.%), a nearly white light emission is observed. The quantum yield of this nearly white light emission is found to be ∼28%. Tunability of the light and white light emission are supported by CIE chromaticity. The energy transfer efficiency from the VO4³⁻ absorption to the excited states of Sm³⁺ ion in YP0.8V0.2O4 reaches upto ∼86% with the doping concentration of 2.25 at.%.
Keywords: Energy Transfer; Luminescence; Multicolor; Nanorod